Enhancing Community Awareness to Avoid Maisir Elements in Transactions: Meningkatkan Kesadaran Masyarakat untuk Menghindari Unsur Maisir dalam Bertransaksi - Ruhliandini, Putri Zafira (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
The main issues in this study are the lack of understanding among residents of Perumahan Ikopin regarding the concept of maisir (gambling/speculative elements) in daily transactions, as well as the prevalence of non-transparent transactional practices that may contain maisir. The absence of education and socialization about the dangers of maisir, coupled with traditional cultural influences, exacerbate the problem. Proposed solutions include seminars, workshops, and discussion groups to raise public awareness. The method used is Participatory Action Research (PAR) with three stages: problem survey, socialization, and evaluation. Results show high participant enthusiasm during discussions, improved understanding of maisir, and no residents involved in online gambling. This activity proves the effectiveness of participatory approaches in transforming transactional behavior